High-voltage electric discharge extraction of bioactive compounds from the cocoa bean shell - Jokić, Stela (Array, 2019)
This study is focused on the application of high-voltage electric discharge (HVED) to recover some bioactive compounds from the cocoa bean shell. Different extraction times (30, 60, 90 min), frequencies (40, 70, 100 Hz) and solvent-solid ratios (10, 30 and 50 mL g–1) were used to obtain cocoa bean shell extracts. Desired bioactive compounds, methylxanthines and phenolic compounds were measured in obtained extracts by high-pressure liquid chromatography with diode array detector. The obtained extracts showed that theobromine was the most abundant, ranging from 2530.13 to 6031.51 mg kg–1, while caffeine content was in the range from 316.08 to 849.88 mg kg–1. In addition, significant amounts of phenolic compounds were found, namely catechin (115.91 to 284.33 mg kg–1), epicatechin (20.20 to 358.90 mg kg–1), and gallic acid (80.28 to 219.17 mg kg–1). Results showed that different parameters of HVED extraction have statistically significant influence on cocoa bean shell composition, suggesting how this byproduct can be used in the production of valuable extracts.